2020
DOI: 10.1002/ccd.29436
|View full text |Cite
|
Sign up to set email alerts
|

Adverse impact of chronic kidney disease on clinical outcomes following percutaneous coronary intervention

Abstract: Aims We aimed to assess the impact of the severity of chronic kidney disease (CKD) with long‐term clinical outcomes in patients undergoing percutaneous coronary intervention (PCI). Methods We analyzed data on consecutive patients undergoing PCI enrolled in the Victorian Cardiac Outcomes Registry (VCOR) from January 2014 to December 2018. Patients were stratified into tertiles of renal function; estimated glomerular filtration (eGFR) ≥60, 30–59 and < 30 ml/min/1.73 m2 (including dialysis). The primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Despite a marked reduction of in-hospital death in patients with renal impairment who received coronary interventional procedures 13 , Sattar et al reported that among patients with severe renal impairment, PCI was performed with less complex anatomy on account of the risks of contrast-induced nephropathy 14 . In a multicenter PCI registry, patients with renal impairment were more likely to develop heart failure, atrial fibrillation, and cardiogenic shock during hospitalization than patients with preserved renal function 15 . Additionally, the severity of renal dysfunction was associated with an increased risk of all‐cause mortality 9 , 14 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a marked reduction of in-hospital death in patients with renal impairment who received coronary interventional procedures 13 , Sattar et al reported that among patients with severe renal impairment, PCI was performed with less complex anatomy on account of the risks of contrast-induced nephropathy 14 . In a multicenter PCI registry, patients with renal impairment were more likely to develop heart failure, atrial fibrillation, and cardiogenic shock during hospitalization than patients with preserved renal function 15 . Additionally, the severity of renal dysfunction was associated with an increased risk of all‐cause mortality 9 , 14 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, renal impairment increases neointimal growth after percutaneous coronary intervention, resulting in higher rates of recurrent restenosis [20]. Previous studies also indicated that renal impairment is significantly associated with an increased incidence of 1-year stent thrombosis in patients undergoing PCI [15,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…VCOR is a state-wide clinical quality registry established to report on and improve the quality of care in cardiovascular disease in Victoria, Australia and has been previously described [ 15 ]. Data on all patients undergoing PCI in 32 public and private hospitals are collected as part of the VCOR PCI module [ 16 ]. The “PCI cohort” in this study included all patients who underwent PCI, comprising those who proceeded with ad hoc PCI (PCI following diagnostic cardiac catheterisation in the same procedure) and patients who had PCI only without preceding cardiac catheterisation.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who undergo PCI procedures and develop CI-AKI are at higher risk of short- and long-term mortality. CI-AKI is also associated with post-PCI cardiovascular events and in-hospital events such as the need for bypass surgery, bleeding and blood transfusion, and other vascular complications [ 8 , 9 ]. Several factors contribute to the development of AKI due to contrast media, such as diabetes mellitus, age, congestive heart failure, and previous history of kidney disease [ 2 ].…”
Section: Introductionmentioning
confidence: 99%